2006
DOI: 10.1017/s1743921307003249
|View full text |Cite
|
Sign up to set email alerts
|

Earth's 2006 encounter with comet 73P/Schwassmann-Wachmann: Products of nucleus fragmentation seen in closeup

Abstract: Abstract. The large numbers of nucleus fragments observed are a spectacular illustration of the process of cascading fragmentation in progress, a concept introduced to interpret the properties of the Kreutz system of sungrazers and comet D/1993 F2. The objective is to describe the fragmentation sequence and hierarchy of comet 73P, the nature of the fragmentation process and observed events, and the expected future evolution of this comet. The orbital arc populated by the fragments refers to an interval of 3.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
0
10
2
Order By: Relevance
“…Similar evidence was found for the broken comet C/1999 S4 (LINEAR): Weaver et al (2001) estimated the separation time from the dynamical properties of 100-m mini-fragments and found that their results indicated an earlier time than the commonly accepted disruption time of C/LINEAR. In addition to the outburst on 1 April, Sekanina (2007) argued that successive outbursts occurred on 24 April and 2 May, although, in Fig. 8, we cannot find evidence for an outburst on 24 April.…”
Section: Interpreting Spatial Distribution Using Modified Synchrones contrasting
confidence: 61%
See 2 more Smart Citations
“…Similar evidence was found for the broken comet C/1999 S4 (LINEAR): Weaver et al (2001) estimated the separation time from the dynamical properties of 100-m mini-fragments and found that their results indicated an earlier time than the commonly accepted disruption time of C/LINEAR. In addition to the outburst on 1 April, Sekanina (2007) argued that successive outbursts occurred on 24 April and 2 May, although, in Fig. 8, we cannot find evidence for an outburst on 24 April.…”
Section: Interpreting Spatial Distribution Using Modified Synchrones contrasting
confidence: 61%
“…Therefore, we can argue that most of minicomets in the southwest were released by an outburst occurring in late March or early April. The onset time of 26 March is earlier than the generally described outburst time of 1 April (Sekanina, 2007). This small discrepancy may imply that these mini-fragments were active and progressive during the early stage of the ejection and became inactive over a one-month period.…”
Section: Interpreting Spatial Distribution Using Modified Synchrones mentioning
confidence: 75%
See 1 more Smart Citation
“…In 1995 while reaching perihelion, SW3 brightened greatly between September 5 and 8 (Crovisier et al 1996), and the first breakup occurred approximately 6 weeks later (Sekanina 1996). Three brightness condensations were found (Boenhardt & Kaufl 1995) in images taken on December 12-13, and several others were found thereafter.…”
Section: Introductionmentioning
confidence: 98%
“…The 2006/2007 apparition was particularly favorable, however, because the comet approached to within 0.08 AU of the Earth when it was near perihelion. During this encounter, the comet was observed to experience multiple cascading fragmentation events (Sekanina, 2007), which were observed by numerous observers worldwide. These observations will provide useful information about the exposure of fresh material, as well as providing constraints on the size distribution of the cometesimals that comprised the nucleus, and the dynamics involved in their breakup.…”
Section: Comet 73p/schwassmann-wachmannmentioning
confidence: 95%